Urgensi Rubrik Berbasis Outcome-Based Education untuk Pendidikan Agama Islam - Makmun Gunawan, Satria Amir; Mustofa, Labib; Zuhriyah, Indah Aminatuz (ALSYS, 2025)
This study is motivated by issues in conventional learning, which remains input-based and is often considered less objective in evaluating student learning outcomes. The Outcome-Based Education (OBE) approach is viewed as a relevant alternative to replace traditional assessment models, particularly through the use of structured and measurable rubrics. This research employs a qualitative approach with a library research design and content analysis technique to examine related literature. The findings indicate that OBE enhances educational quality by emphasizing concrete learning outcomes that align with contemporary needs and promote more flexible, active, and innovative learning. This approach can be implemented across all levels of education, including primary education, with rubrics serving as objective evaluation tools. The study affirms that rubrics within the OBE framework are highly applicable to the Akidah Akhlak subject in Madrasah Ibtidaiyah, as they enable more structured and fair assessment of students’ affective domains. The implication is that implementing OBE from early education opens opportunities for learning evaluation that balances both process and outcome orientation. Furthermore, the study recommends further research to explore practical implementation and the contextual assessment of student character using more applicable instruments.